Can Freshman Science Student Teachers’ Alternative Conceptions of ‘Electrochemical Cells’ Be Fully Diminished? - Karsli, Fethiye; Çalik, Muammer (Asian Journal of Chemistry, 2011)
The purpose of this study is to investigate effect of 5E learning model incorporating in different conceptual change methods such as computer animations, conceptual change text, worksheet and hands-on activities on remedial program for freshman science student teachers (FSSTs) alternative conceptions of 'electrochemical cells'. The sample of the study consisted of 30 freshman science student teachers (21 girls and 9 boys - aged 18 to 22 years) enrolled in 'general chemistry laboratory' course. An electrochemical-cells concept questionnaire with 6 two-tier questions was employed as pre-, post- and delayed-test. Results showed that the 5E learning model not only helped the freshman science student teachers overcome their alternative conceptions but also store them in long term memory. Needless to say, due to the 5E learning model with different conceptual change methods, some of the freshman science student teachers alternative conceptions have still been robust to be diminished fully.